Liquidity and Leverage Effects on Sudatel’s Financial Performance (2015–2024) - Elgadi, Najla FatehElrhman (Journal of Economic, Administrative and Legal Sciences, 2025)
This study examines the effect of liquidity and financial leverage on the financial performance of Sudatel Telecommunications Group Ltd. over the period 2015–2024, a time marked by economic and financial instability in Sudan. A descriptive–analytical approach was employed, using SPSS to conduct correlation analysis, linear regression, and ANOVA. The results reveal a strong and statistically significant positive relationship between liquidity and financial performance. Specifically, the Quick Ratio emerged as the most influential predictor of Return on Assets (ROA), with a regression coefficient of 5.698 at a significance level of 0.013. In contrast, financial leverage showed no significant effect on ROA (P = 0.470), indicating that debt financing did not contribute to profitability. Earnings per Share (EPS) also exhibited no significant impact, underscoring its dependence on external market factors. By distinguishing between liquidity measures and providing context-specific evidence from Sudan’s telecommunications sector, this study addresses a research gap in fragile economies. It recommends strengthening quick liquidity management, minimizing reliance on debt, and improving working-capital efficiency to enhance financial resilience.